Enhancement of digital signature algorithm in bitcoin wallet - Farah Maath Jasem; Ali Makki Sagheer; Abdullah M. Awad (Institute of Advanced Engineering and Science, 2021)
Bitcoin is a peer-to-peer electronic cash system largely used for online financial transactions. It gained popularity due to its anonymity, privacy, and comparatively low transaction cost. Its wallet heavily relies on elliptic curve digital signature algorithm (ECDSA). Weaknesses in such algorithms can significantly affect the safety and the security of bitcoin wallets. In this paper, a secure key management wallet was designed based on several changes in the wallet parts. In the cold wallet, we employed an image-based passphrase to achieve a strong entropy source of master seed. The hot wallet, the proposed Key_Gen algorithm is modifying to the key generation step of the ECDSA that it is to generate a fresh key pair at each transaction. The final part ensures recovering all keys on both hot and cold wallets without daily backups in case of losing the wallet. The findings prove that the proposed cold wallet is resisting against a dictionary attack and overcoming the memorizing problem. The proposed hot wallet model acquires good anonymity and privacy for bitcoin users by eliminating transaction likability without additional cost. The execution time for signing a transaction of the proposed model is 70 millisecond, which is then important in the bitcoin domain.